Determination of efficiency of investments in construction - Ustinovichius, Leonas (International Journal of Strategic Property Management, 2004)
Decision making is associated with ranking problems aimed to obtain a set of preference order of solutions. People can make mistakes choosing the best object for investments. Due to high cost of such mistakes, such a choice should be well founded. A major goal of paper is to develop a theoretical basis for creating a decision support system aimed to increase building construction and reconstruction investment efficiency by applying multiattribute decision making approaches and mathematical modelling. To achieve the goal, the following problems have to be solved: to analyse new models currently used in developing investment strategies in building construction and reconstruction, to make a classification of construction investment projects and to describe the stages of determining the efficiency of construction investments, to create a family of multiattribute decision methods to be used in the analysis of investment projects in building construction and reconstruction, to create multiple attribute decision support system based on the multiattribute methods developed for determining the efficiency of construction and reconstruction investment projects. First Published online: 18 Oct 2010